Heat transfer to graphene nanoplatelets and metaloxides-studies in thermophysical properties and particle characterization / Solangi Khalid Hussain - Solangi Khalid , Hussain (2016)
Nanofluids investigated in the present study are suspensions of highly conductive particles in base fluids that exhibit enhanced suspension thermal properties at modest nanoparticle concentrations. Specific nanofluids have unique heat transfer properties and are utilized in high heat flux systems (e.g., electronic cooling systems, heat exchanger liquids, solar collectors, and nuclear reactors). This study has focused on heat transfer and friction loss characteristics of propylene glycol-Treated Graphene Nanoplatelets (PGGNP-water), trimethylolpropane tris [poly(propylene glycol), amine terminated] ether-Treated Graphene Nanoplatelets (TMP-treated GNP-water), Al2O3 and SiO2 water based nanofluids. In this investigation the convective heat transfer in circular tubes of different diameters and materials were considered at constant wall heat fluxes of 23870 W/m2 and 18565 W/m2. The experiments were conducted at the Reynolds number range of 3,900–11,700. A novel functionalization approach for preparing highly dispersed PGGNP-Water and TMP-treated GNP-water were developed. Characterization instruments showed a good degree of GNP functionalization with PG and TMP functionality. Stability study showed more than 88% of both PGGNP-water and TMP-treated GNP-water dispersed even after 1 month. In the materials effect study of the test sections the copper material showed highest heat transfer performance while in size effect study the lowest diameter of the test section showed the maximum increment in heat transfer performance. In this research all the prepared nanofluids have provided significant enhancement in heat transfer characteristics. The measured thermal conductivity, viscosity, specific heat capacity and density of all the samples showed reasonable required performance for a good heat exchanging liquid. Heat transfer and friction loss experiments were conducted in closed conduit (pipe) flow with distilled water for validation of experimental data. The impact of the dispersed nanoparticles concentration on thermal properties, convective heat transfer coefficient, Nusselt number, Friction factor, performance index, pumping power and efficiency of loop were systematically investigated. The enhancement in thermal conductivity of PGGNP-water was observed in between 20% and 32% (0.025-0.1wt%, 20-50oC), compared to base fluid. Among all the tested nanofluids the PGGNP-water at 0.1wt% showed the maximum, 119% enhancement in heat transfer coefficient compared to that of the base fluid whereas the TMP-treated GNP-water showed enhancement in heat transfer coefficient up to 107%. Beside GNPs, Al2O3 and SiO2 nanofluids also showed good enhancement in heat transfer coefficient up to 29% and 31.6% respectively at 0.1 wt% concentrations. The maximum increment in Nusselt number was observed up to 82% in PGGNP-water at the heat flux of 23870 W/m2. The performance index and pumping power showed a positive effect over all types of tested nanofluids. The results indicated that both the Nusselt number and the friction factor of the nanofluids increase with the increasing of particle volume concentration and Reynolds number. However, by increasing little amount of concentration has shown much effect on heat transfer enhancement. The ultimate goal is to disseminate the understanding of the mechanisms of the colloidal behavior of the nanoparticles as well as to broaden the experimental database of these new heat transfer media. It appears that functionalized GNPs, Al2O3 and SiO2 nanofluids could be recommended as a heat exchanging fluid which could be a potential alternative to the presently used conventional working fluids.